Second trimester amniocentesis for prenatal diagnosis of genetic disorders in Bangladesh - Kazal, Rezaul Karim; Chowdhury, Saima Akhtar; Pervin, Tabassum; Pervin, Hasna Hena; Kaniz, Paromita Waheeda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Amniocentesis is characteristically carried out under ultra-sonographic control, between 15 and 17 weeks of pregnancy. The term prenatal diagnosis firmly comprises all diagnostic modalities aimed at gaining information about the embryo. Its history includes the development of cytogenetic, molecular genetics and molecular cytogenetic methods. Prenatal diagnosis is now possible for a considerable number of genetic diseases and/or birth defects using a variety of techniques. Objective was to evaluate the safety, feasibility and outcome of second trimester amniocentesis for prenatal diagnosis of genetic disorders. Methods: This was a descriptive study, conducted at fetal medicine center, Family Care Foundation, Dhaka, Bangladesh from June 2014 to December 2019. A total of 350 pregnant women had undergone 15-20 week’s transabdominal amniocentesis under real-time ultrasound guidance. A 23 gm/ 88 mm spinal needle was used. The needle was passed though the maternal abdomen into the amniotic cavity in its longitudinal direction. Once the needle was adequately placed, the amniotic fluid is aspirated with a suction force through a 20 cc syringe. All amniocentesis was performed with “two operators” technique. Results: A total of 350 Amniocentesis were done. Beta thalassemia was most common (79.7%). Followed by aneuploidy (10.2%), hemophilia (6.2%), SMA (2.0%), DMD (1.7%), hematoma (7%), intra amniotic bleeding (2%) and per vaginal bleeding (2.8%). 3.7% aspiration was difficult due to fibroid and retroverted uterus. The overall aspiration success rate was 100%. Conclusions: Second trimester transabdominal amniocentesis in an outdoor setting with the help of real-time sonography is a safe procedure with no significant risk to the mother and the fetus.